The neutrophil antimicrobial peptide cathelicidin promotes Th17 differentiation - Danielle Minns (Nature Portfolio, 2021)
Neutrophils secrete numerous immune effector molecules including cathelicidin which is associated with antimicrobial properties. Here the authors implicate neutrophil derived cathelicidin in modulation of CD4 T cell homoeostasis and the promotion of Th17 CD4 T cells.